2005
DOI: 10.1037/0021-843x.114.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Context Insensitivity in Major Depressive Disorder.

Abstract: The present study tested 3 competing views of how depression alters emotional reactivity: positive attenuation (reduced positive), negative potentiation (increased negative), and emotion context insensitivity (ECI; reduced positive and negative). Normative and idiographic stimuli that elicited happy, sad, and neutral states were presented to currently depressed, formerly depressed, and healthy control individuals while experiential, behavioral, and autonomic responses were measured. Currently depressed individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

95
481
15
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(606 citation statements)
references
References 63 publications
(102 reference statements)
95
481
15
3
Order By: Relevance
“…ANOVA conducted with response frequency as the dependent variable showed a main effect of picture category (F [2,76] = 7.68, p = 0.001), reflecting that pleasant and unpleasant pictures induced more responses that neutral ones (t [38] = 4.75, p < 0.001 ; t [38] = 4.62, p < 0.001). Although the group × picture category did not reach significance (F [2,76] = 0.99, p = 0.37) but because of specific expectations regarding emotional differences between depressed and control subjects, paired comparisons were carried out, and showed that pleasant pictures elicited more responses than the unpleasant ones in control (t [38] = 2.66, p = 0.01) but not in depressed subjects (t [38] = 0.11, p = 0.91).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ANOVA conducted with response frequency as the dependent variable showed a main effect of picture category (F [2,76] = 7.68, p = 0.001), reflecting that pleasant and unpleasant pictures induced more responses that neutral ones (t [38] = 4.75, p < 0.001 ; t [38] = 4.62, p < 0.001). Although the group × picture category did not reach significance (F [2,76] = 0.99, p = 0.37) but because of specific expectations regarding emotional differences between depressed and control subjects, paired comparisons were carried out, and showed that pleasant pictures elicited more responses than the unpleasant ones in control (t [38] = 2.66, p = 0.01) but not in depressed subjects (t [38] = 0.11, p = 0.91).…”
Section: Resultsmentioning
confidence: 99%
“…ANOVA conducted with response amplitude as the dependent variable showed a main effect of picture category [38] = 2.76, p < 0.01) but not in depressed subjects (t [38] = 0.54, p = 0.59). These effects were not modulated when relevant personality scores were controlled (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For now, two elements have to be considered: On the one hand, depression is characterized by avoidance behavior (see Ottenbreit & Dobson, 2004;Trew, 2011, for reviews), which goes along with a preserved motivation to avoid punishments. On the other hand, avoidance behavior in depression is of a passive, maladaptive nature: Indeed, depression is characterized by disengagement (Rottenberg, Gross, & Gotlib, 2005), by hopelessness (Abramson, Seligman, & Teasdale, 1978), and by a strong behavioral inhibition system, which leads to passive avoidance (Fowles, 1994). Taking these elements together, we expect individuals with depression to be motivated to avoid a punishment but to show a passive avoidance behavior in anticipation of that punishment, which prevents them from successfully avoiding it.…”
Section: Reward and Punishment Anticipation In Depressionmentioning
confidence: 99%